Case conference concerning 9-year-old boy having 20 mmol/lcholesterol: from diagnosis to effective treatment - AV Susekov; ZG Luginova; AN Meshkov; EY Solovyova; TV Balakhonova; MA Saidova; TI Kotkina; MY Scherbakova; VV Davydkin; MA Dubovenko; AY Postnov; ZB Khasanova; et al. (Медицинский совет, 2014)
Familial hypercholesterolemia (FHC) is the most common and most severe form of monogenic dyslipidemia with early and rapidly progressing atherosclerosis and its complications [1--4, 12, 14]. Without treatment, the prognosis for patients with FHC is as heavy as for AIDS patients. For the first time the molecular defect - absence or dysfunction of the LDL receptor (LDL-R), the main route for cholesterol catabolism in humans [2, 3, 12, 13] - was described with regard to this genetic disease. The article analyzes a clinical case of the disease in a 9-year-old boy.